Penghayatan fardu ain remaja pekak di Malaysia / Mohd Huzairi Awang @ Husain - Mohd Huzairi , Awang @ Husain (2017)
This study aims to assess the level of knowledge and internalization of Fardu Ain among deaf teenagers, and the relationship between the practice of learning, learning environment and their perception of learning with knowledge and internalization of Fardu Ain and their perception towards knowledge acquisition and internalization of Fardu Ain, as well as studying the relationship between knowledge acquisition and the internalization of knowledge Fardu Ain among deaf teenagers. This study was conducted at two Special Education Secondary Schools (hearing impaired). This study is a survey using a questionnaire. A total of 89 deaf teenagers from all over Malaysia have participated in this study. The data were analyzed through descriptive analysis (mean, frequency and percentage) and inferential analysis (Pearson Correlation). The study found that the practice of learning, learning environment and perceptions of deaf teenagers learning Fardu Ain are at a low level. The knowledge acqusition and internalization of Fardu Ain were also at a low levels. Pearson correlation analysis showed there was a correlation between the practice of learning, learning environment and perceptions of learning with knowledge acquisition and internalization of Fardu Ain respondents. There is also a relationship between knowledge acquisition and the Fardu Ain internalization among deaf teenagers. This study is also enriched with data interview involving 3 teachers as the study participants and 4 students who were randomly selected. The findings of qualitative data found there was alignment with the findings of qualitative data in some aspects. This demonstrates the need for improvement of Fardu Ain teaching approaches, respondents' perceptions and learning practices, and providing a conducive environment to learn Fardu Ain. The findings also suggest guidelines in teaching and learning of Fardu Ain for deaf teenagers in Malaysia.